Potential Co-Factors of an Intraoral Contact Allergy-A Cross-Sectional Study - Constanze Olms; Jana Schor; Maryam Yahiaoui-Doktor (MDPI AG, 2020)
The aim of this cross-sectional study was to evaluate the frequency of dental allergens and potential co-factors, especially hypothyroidism, for patients with an intraoral contact allergy. From 2015 to 2016, patients with confirmed symptoms of an intraoral contact allergy (study group SG n = 50) were recruited in the dental clinic of the University of Leipzig. The participants of the control group (CG n = 103) were patients without oral diseases or intraoral symptoms of a contact allergy. For the data collection, a new "Allergy questionnaire" was developed. Information on allergies and general diseases were collected. The statistical analysis was carried out with SPSS 23.0. Sensitizations/allergies to metals and composites were higher in SG compared to CG. Of all study participants (n = 148), 14.2% (n = 21) had a nickel allergy. In 18% (n = 8) of the SG a cobalt allergy based on all metal allergens could be seen. In addition, an association between a nickel and cobalt allergy was found. Hypothyroidism occurred significantly more frequently (p = 0.049) in SG than in CG. Sensitizations and allergies can occur to metals in dental alloys. Hypothyroidism increased the risk of having an allergy threefold.